Where Are We Now: A Literature Review of Agency Theory on Finance and Accounting within Tourism and Hospitality Industry - Handyastuti, Indriyani; Waspada, Ikaputera; Sari, Maya (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2023)
Purpose of the study: The purpose of this study is to investigate attentively works about Agency Theory and financial and accounting management in the Tourism, Hospitality, and Hotel Industry. Design/methodology: This research adopts a literature search utilizing Bibliometric analysis to identify publications on Agency Theory within the tourism and hospitality industries and analyses research journals as the foundation for additional research on the subject at hand. Findings: Data regarding name, date of the journals, certain industry and scope of area that discussed in these journals, focus of the research and data analysis. This study identified previously unexplored topics and suggested further study based on the analysis procedure. Research limitations/Implications: Since data are very limited therefore VOSviewer application cannot be used. This research limited only with manual analysis using Microsoft Excel. Novelty/Originality of the study: Agency theory has also has been researched from various point of view. Note only finance and accounting, but also Law, Sociology, Entrepreneurship, Marketing and from the Islamic Shariah point of view. However, there are no studies found analyse Agency Theory on financial and accounting management in fields of Tourism, Hospitality, and Hotel Industry. This research is trying to fill in the gap.